2015
DOI: 10.2214/ajr.14.13865
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ROI Positioning and Lesion Morphology on Apparent Diffusion Coefficient Analysis for the Differentiation Between Benign and Malignant Nonfatty Soft-Tissue Lesions

Abstract: The ADCmin values obtained with manual ROI positioning offered the best diagnostic performance for tumor characterization. The semiautomatic method yielded similar specificity values. For solid masses, the ADCavg values were better correlated with tumor histology than the ADCmin values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…We believe one of the possible reasons for this is the difference in ROI selection. 29 In our study, the ROIs covered the whole tumor, including heterogeneous cellularity, calcification, hemorrhage, or necrosis; consequently, the DDC min may not well represent the components densely packed with malignant cells. Another possible reason is that the minimums are highly sensitive to noise in the maps, whereas 10 th percentiles are not.…”
Section: Discussionmentioning
confidence: 82%
“…We believe one of the possible reasons for this is the difference in ROI selection. 29 In our study, the ROIs covered the whole tumor, including heterogeneous cellularity, calcification, hemorrhage, or necrosis; consequently, the DDC min may not well represent the components densely packed with malignant cells. Another possible reason is that the minimums are highly sensitive to noise in the maps, whereas 10 th percentiles are not.…”
Section: Discussionmentioning
confidence: 82%
“…Quantitative assessment of nodules on DWI relies on ADC measurement. It has been shown that the ADC min values are more successful than mean ADC (ADC mean ) values for the malignant and benign tumor differentiation . Park et al showed that the use of ADC min may allow better performance than ADC mean in predicting of Gleason score in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DWI is new method used to differentiate benign from malignant soft tissue lesions based on ADC values; quantitative DWI are useful for differentiating between malignant and benign superficial masses [12][13][14] . In this study, 500s/mm 2 of b value was performed and mean ADC value of solid GCT-ST lesions was 2.19×10 −3 mm 2 /s, which was higher compared to the surrounding normal soft tissue.…”
Section: Discussionmentioning
confidence: 99%